CRITICAL PATIENTS AND AEROBIC ACTIVITY: AN ANALYSIS OF HEMODYNAMIC VARIABLES (Fiep Bulletin - online, 2013)
The acquired immobility to critical patients in the intensive care units (ICU), reduces endurance and muscle strength, compromises the blood supply, develop generalized muscle weakness, resulting in poor quality of movement and makes it difficult weaning from mechanical ventilation. Exercise increases  tone and contraction muscle as well as facilitating venous return, prevents and reduces the formation of edema.  AIM: Evaluate the hemodynamic responses and lower limbs volumetric in critically ill patients who underwent physical training in the ICU. METHODS: Qualitative research like case study, convenience sample by 02 critically ill patients in ICU.The physical training consisted of five sessions of aerobic exercise for lower limbs (MMIIs) at 20 minutes. The variables analyzed were: systolic and diastolic blood pressure (SBP and DBP, respectively), heart rate (HR), respiratory rate (RR), oxygen saturation (SpO2), water fluid balance and volume of MMIIs. RESULTS: The water fluid balance and the MMIIs volumetric showed a positive association, independent of edema formation. HR and RR were characterized as provided for in healthy subjects and SpO2 remained stable. SBP and DBP were characterized by divergent among patients, especially the DBP during the aerobic exercise. CONCLUSION: The physical training for patients in the ICU does not appear to significantly change from hemodynamic variables. The fragility of the number of sample in this study is an important aspect and despite to show himself as a safe therapeutic further investigation will be required about aerobic activity in critically I ll patients.
Keywords: Intensive Care Units; Hemodynamics; Exercise